Ultrasound-Assisted Methyl Esterification of Carboxylic Acids ACatalyzed by Polymer-Supported Triphenylphosphine - Subin Jaita (2018)
© Georg Thieme Verlag Stuttgart · New York. A convenient and efficient sonochemical method for methyl esterification of carboxylic acids catalyzed by polymer-supported triAphenylphosphine (PS-Ph3P) is reported. In the presence of 1:0.1:2 molar ratio of 2,4,6-trichloro-1,3,5-triazine/PS-Ph3P/Na2CO3, methyl esters of various carboxylic acids bearing reactive hydroxyl groups as well as acid-or base-labile functionalities could be rapidly prepared (within 10-20 min) in good to excellent yields without necessity to pre-activate the acids. Using the polymer-bound phosphine also allows easy isolation of the products which, in most of the cases, were obtained in high purities without column chromatography.